Abnormal Neurologic and Motor Function in Newborns Treated for Congenital Syphilis - Bruna Silva; Luciana Friedrich; Graziela Biazus; Renata Bueno; Carla Almeida (Infectious Disease Reports)
Background: Congenital syphilis (CS) is a transplacental infection that can lead to many long-term sequelae when not adequately treated; however, knowledge about the motor and neurological signs that newborns (NBs) with CS may present is scarce. Objective: The aim of this study was to describe the results of neurological assessment scales and general movements in NBs with CS in the first days of life. Methods: In this case-series, the Hammersmith Neonatal Neurological Examination (HNNE) and General Movements Assessment (GMA) scales were used to evaluate NBs under treatment for CS in a public Brazilian hospital in the first days of life. Results: The sample consisted of 11 NBs, with a mean birth weight of 3140.5 g, and an Apgar score at 5 min of 8.3. Among the 11 mothers, 4 (36.4%) had fewer than six prenatal visits and 5 (45.5%) did not receive any syphilis treatment. All NB (100%) were asymptomatic, with normal long bone X-rays and cerebrospinal fluid analysis. The mean score on the HNNE was 22 (suboptimal/abnormal). Eight NBs (72.7%) showed abnormalities on GMA scale (with six [54.5%] being mildly abnormal and two [18%] definitely abnormal). Only three NBs (27.3%) returned for outpatient follow-up. Conclusions: Neurological and motor evaluations were abnormal in most of the asymptomatic NBs under treatment for CS in the first days of life, when assessed through specific scales (HNNE and GMA). Most mothers did not receive adequate treatment for syphilis during pregnancy, and there were important deficiencies in post-discharge follow-up. Further studies are needed to confirm these findings and investigate whether the observed abnormalities are linked to biological or environmental factors during pregnancy.